Nanofluid-based Nanocarbons An Investigation of Thermal Conductivity Performance - Imran Syakir, Mohamad; S. B., Abdul Hamid; W. M. , Chin; K. H., Yau; A., Samsuri (Penerbit Universiti Teknikal Malaysia Melaka, 2011)
This paper presents a study of thermal conductivity performance, using a nanofluid-based nanocarbon formulate, with three different types of nanocarbons. NC300, NC200, and commercial carbon nanotube (CNT)were used together with Sodium Dodecyl Sulphate (SDS) as a dispersant, and deionized water as a solvent. A weighted ratio of the nanocarbons (0.4 - 1.0wt%) was set-up and the thermal conductivity was measured at 6°C, 25°C, and 45°C using a KD2 Pro thermal properties analyser. The results showed that NC300 with 1wt% of nanocarbons at 45°C gave the highest improvement of almost 30%, compared to deionized water. Meanwhile, the best nanofluid, based on prepared nanocarbons (NC200) and commercial CNT, showed improvement of more than 9% and 12%, respectively, with the addition of 0.6wt% nanocarbons at 45°C. Morphology analysis using electron microscopy, revealed the structural properties of the nanocarbons. NC300 showed a loose CNT with an average diameter of 70-150nm. NC200 are supported by nanocarbons with an average diameter of 10- 30nm. Meanwhile, the commercial CNT showed a similar characteristic to that of NC300. Even though NC200 had the smallest diameter of all nanocarbons, (which should provide the highest surface area), the larger sizes of the activated carbons, as a nanocarbon support, are expected to reduce thermal conductivity performance.